2017
DOI: 10.1515/sjph-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the association between dentate status and self-rated general health

Abstract: ObjectiveAiming at preparing the basis for evidence-based dental public health policy making in Slovenia, the objective of the study was to assess the strength of association between oral health status measured by the number of missing teeth and self-rated health (SRH).MethodsThe study was designed as a pooled individual-level data study from four national cross-sectional studies carried out in the period 2001-2012, based on CINDI Health Monitor methodology. Altogether, 34,412 participants were included. A log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Tyrovolas et al, showed a link between tooth loss, SRH and depression in low‐ and middle‐income countries. Ranfl et al also found a strong association between tooth loss and SRH, after adjustment for confounders in Slovenian adults, consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tyrovolas et al, showed a link between tooth loss, SRH and depression in low‐ and middle‐income countries. Ranfl et al also found a strong association between tooth loss and SRH, after adjustment for confounders in Slovenian adults, consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Empirical research has previously investigated the associations between oral and general health outcomes, mostly showing correlations with noncommunicable diseases (eg, stroke, diabetes) . To a lesser extent, specific proxies of long‐term oral health (such as tooth loss and edentulism) have been correlated with general health, taking a broad definition of the latter . Tyrovolas et al, showed a link between tooth loss, SRH and depression in low‐ and middle‐income countries.…”
Section: Discussionmentioning
confidence: 99%
“…As 56% of schoolchildren with mixed dentition and 46% of schoolchildren with permanent dentition have caries, one can assume that the overall orthodontic treatment need in population might be lowered if caries prevention and timely treatment were employed ( 27 ). Recent research showed strong correlation between the oral health and number of preserved teeth and self-reported general health ( 28 ). This indicates that putting the emphasis on the caries prevention and teeth preservation should be a continuous public health agenda of greatest importance.…”
Section: Discussionmentioning
confidence: 99%
“…Reissmann et al used OHIP-49 and SF-36 PROMs, while we used OHIP-49 and PROMIS v.1.1 Global Health PROMs. Similarly, the study by Ranfl and Zaletel-Kragelj used single items for the evaluation of the connection between dentate status and self-assessed general health on a large sample of general population subjects (11). Like us, they also considered the possibility of variation in data when adjusted for confounders such as age, gender, educational level, type of work, and self-classified social class (11).…”
Section: Discussionmentioning
confidence: 99%
“…Zimmer et al derived a correlation between OHIP-14 and SF-12 scores of 0.31-0.32 (9), while Reissmann et al reported a slightly higher correlation of 0.40 between OHIP-49 and SF-36 scores (10). Ranfl and Zeletel-Kragelj assessed the association between self-rated dentate status and self-rated general health and concluded that poor self-rated health was associated with a higher number of self-reported missing teeth (11).…”
Section: Introductionmentioning
confidence: 99%